The Effect of Employee Performance and Service Quality on Customer Satisfaction at Snacks at Indofood Fortuna Makmur Sales Poin Sidoarjo - Tafsiri, Gathut Anang; Utomo, Priyo (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: To determine the effect of employee performance and service quality on customer satisfaction at Indofood Fortuna Makmur Company. Design/Methodology/Approach: Descriptive quantitative methods were used in this study. The research instrument was a questionnaire distributed to participants. All participants in the current research were company staff members. Indofood Fortuna Makmur Company, with a population of 1,130 and a sample of 296. Data analysis techniques used regression and data processing with the help of SmartPLS 4.0 software. Findings: Employee performance has a positive and significant effect on customer satisfaction. This is evidenced by the path coefficient value of 0.075, t-statistic of 2.209 (>1.96), and p-value of 0.027 (<0.05). Service quality has a positive and significant effect on customer satisfaction, with a path coefficient value of 0.803, t-statistic of 42.177, and p-value of 0.000. Employee performance and service quality simultaneously have a significant effect on customer satisfaction. This is evidenced by the R-Square value of 0.682, which means that 68.2% of the variation in customer satisfaction can be explained by these two variables. This demonstrates how, all at once, the variables of employee performance (X1) and service quality (X2) have a favorable and noteworthy impact on the performance of employees (Y) at Indofood Fortuna Makmur Company. Research limitations/implications: The findings of this study are expected to be used as a reference by subsequent researchers. Practical implications: With the findings of this study, it is expected that Indofood Fortuna Makmur Company .can create a supportive work environment, improving optimal employee performance. Originality/value: The present research is the initial inquiry carried out by researchers. at Indofood Fortuna Makmur Company on employee performance. Paper type: Research paper